Use of Fertilizers in Eucalyptus Plantations - Sinha, B. N. (Indian Forester, 1970)
Eucalyptus hybrid (Syn. E. tereticornis or Mysore gum) has been planted as a fast growing species in many States. Experiments in different States have been going on to find out methods to increaae its yield and the use of fertilizers is one of the methods which can be used with advantage. Experiments indicate that fertilizers increase the height and diameter of the plants significantly, the dose of fertilizers depending upon the soil type. The results of 3 fertilizer experiments carried out in Bihar are reported and tentative suggestions made for the application of fertilizers in these 3 types of soil.